A influência do estoque de capital humano sobre a produtividade individual: uma análise para as capitais brasileiras - Mattei, Tatiane Salete (2018)
The objective of this essay is to estimate if there is influence of the stock of capital human and its externalities about the productivity of the workers of the capitals of the Brazilian states for the year 2015. Brazil presents differentials of high education levels, influencing large inequalities in the income distribution of the population, also reflecting a significant incidence. This essay has as main theoretical basis the Human Capital Theory, which argues that the education and experience of the population are responsible for productivity differentials, rai sing workers' income. The rising in come of families increase the consumption, and consequently brings a higher quality of life. Thus, for this purpose will be estimated Mincerian equations of income, beyond equations for each sector of individual economic activity sector. The data used in the research come from the RAIS- Relação Anual de Informações Sociais (Annual Report of Social Information), developed by the Ministry of Labor. The hypothesis considered is that regions with larger stocks of human capital are more productive for all groups of works, inclusive those with less schooling, because generate an effect spillover. The essay becomes relevant both for public policy makers and for Brazilian workers. By demonstrating that human capital contributes to improving people's quality of life, formulators of public policies could concentrate the public resources on education area, and to make with more responsibly and efficiently, reducing income inequalities in the country. For workers it can be an incentive to study and specialize in the pursuit of social mobility. The results show that the education of the workers, their acquired experience and the externalities of the human capital act positively for the determination of the productivity, this form can be conclude that the standing hypothesis in essay is accepted. Access to quality education also have a positive influence on the determination of workers' wages. The agglomerations and cost-of-living differentials did not present expected results, and did not influence the determination of productivity in the model. The signs of the coefficients infer that workers had higher wages due to local amenities, in other words, when the local presents bad characteristics with congestion, pollution and lack of recreation options. In addition, there is discrimination between men and women and between blacks and whites in the model, and that the sectorial affiliation of workers presented significant impacts on the determination of wages. Thus, there is the necessity that should beoffered the population opportunities for access and quality education and that people invest their time and money in education and experience in order to earn higher incomes and consequently social mobility.